68Ga‐Ca‐phytate particles: A potential lung perfusion agent of synthetic origin prepared in a cold kit format. (8th September 2016) - Hsieh, William; Ali, Masood; Praehofer, Renee; Tsopelas, Chris
Abstract : The objective of this study was to investigate the radiosynthesis of 68 Ga‐Ca‐phytate particles and then characterize the formulation for radiochemical purity, radioactive particle size distribution, and biodistribution in normal rats. This radiotracer was prepared using a commercial phytate cold kit after reconstitution with saline, 68 Ga‐chloride generator eluent, calcium chloride, and air, then heating at 100°C for 30 minutes to achieve 99% radiochemical purity of 68 Ga‐particles that were 21% 3–5 μm, 8% 5–15 μm, and 71% >15 μm in diameter. This optimal formulation was stable for 2 hours at room temperature. Intravenous administration of 68 Ga‐particles in rats resulted in an uptake of 93% in the lungs, 4% in the liver plus spleen, and 3% in the carcass after 20 minutes. Two‐thirds of the carcass activity was radioactive blood, likely to be 68 Ga‐transferrin. The positron emission tomography image was superior than the 99m Tc‐MAA image because it displayed high lung uptake against a low background. Low uptake by the liver, spleen did not interfere with the diagnostic quality, and faint activity in the submandibular (salivary) glands was due to 68 Ga‐transferrin. The preclinical data so far indicate that 68 Ga‐Ca‐phytate particles have good potential as a lung perfusion imaging agent. Abstract : The aim was to prepare 68 Ga‐Ca‐phytate particles from 68 Ga‐chloride generator eluate. A commercial phytate cold kit containing stannous ions was reconstituted with 68 Ga‐chloride and calcium chloride, then heated at 100°C for 30 minutes with air. The optimal product formulation was prepared in 99% radiochemical purity with 71% particles >15 μm in size. Radiotracer biodistribution in normal rats was quantified as 93% lungs uptake, 4% liver, and 0.3% in the spleen at 20 minutes post‐intravenous injection. Pulmonary uptake dominated the positron emission tomography scan with faint uptake in the salivary glands. 68 Ga‐Ca‐phytate is a potential lung perfusion agent of synthetic origin.